Growth Performance of Cenchrus bilforus Roxb and Chrysopogon aciculatus [Retz.] Trin: On Soil Polluted with Waste Engine Oil - Ifediora, N. H.; Rowland, C. G. (Cutting Edge Research in Biology Vol. 4, 2023)
Growth performance of Cenchrus bilforus and Chrysopogon aciculatus grown on waste engine oil-polluted soil was carried out as an environmental assessment indicator of the unrestained dumping of waste engine oil on the soil by the motor mechanics in Nigeria. The aim of the work was to investigate the growth tolerance of C. bilforus and C. aciculatus grown in the soil polluted with waste engine oil. The experiment was laid out as a completely randomized design (CRD) in 3 replicates. Waste engine oil from patrol car engines was added to four (4) kg dry soil samples at different concentrations on weight basis: 0% (control), 3%, 6% and 9% w/w oil-in-soil and allowed to stand for seven days before transplanting. The plants were harvested after 8 weeks of transplanting. The result showed that the highest plant height values were 70.33 cm (C. bijlorus) and 41.8 cm (C. aciculatus) respectively in the 3% contamination while lowest values of 19 cm (C. bijlorus) and 0.3 cm (C. aciculatus) were both recorded in 9% contamination at week 8. The highest leaf area value was 12.6 cm (C. bijlorus) and 1.74 cm (C. aciculatus) in 3% contamination and control while the lowest values of 11.08 cm (C. bijlorus) and 0.17 cm (C. aciculatus) were both recorded in 6% contamination at week 8. The leaf number, C. bijlorus and C. aciculatus gave the highest value of 23.33 cm and 16 cm at control and 3% pollution while C. bijlorus and C. aciculatus gave the lowest value of 11.67 cm and 0.33 cm at 6% and 9% pollution at week 8. The shoot girth, C. bijlorus and C. aciculatus gave the highest value of 1.2 cm and 1.1 cm at control respectively while C. bijlorus and C. aciculatus gave the lowest value of 0.73 cm and 0.17 cm at 6% and 9% pollution at week 8. The growth parameters reduction with increase in the levels of pollution was very significant (P<0.05). In conclusion, the two-grass species studied showed evidence of phytoresponse to low levels waste engine oil pollution but C. aciculatus could not with stand higher percentages of waste engine oil.